Effect of different storage period on seed quality of rice cv. MR220 / Nik Nurul Aqilah Che Mat Nasir - Che Mat Nasir, Nik Nurul Aqilah (Faculty of Plantation and Agrotechnology, 2018)
This research was conducted to determine the effect of different storage period on rice seed quality of cv. MR220. The objectives of this study are to determine the ability of rice seed to germinated normally as affected by different period of storage and also to determine the changes of seed moisture content by different period of storage. The seed sample was obtained from KADA at different duration of 2, 4 and 7 months. The rice seed quality of the different storage period which are 2 months, 4 months and 7 months were research for seed moisture content (%), seed electrical conductivity (μs/cm/g), seed thousand (1000) dry weight (g) and ability of seed to germinated normally (%). Data were collected with three replications per treatment. Data was analyzed using SPSS software version 20. The results showed that electrical conductivity of seed, seed dry weight and ability of seed germinate normally were significantly affected by different storage period except for seed moisture content. For 2month storage period, the seed moisture content is 8.27%, seed electrical conductivity 0.015μs/cm/g, seed thousand (1000) dry weights is 28.94g, and ability of seed to germinate normally is 50%. For 4month storage period, the seed moisture content is 6.75%, seed electrical conductivity 0.017μs/cm/g, seed thousand (1000) dry weights is 30.13g, and ability of seed to germinate normally is 80.66%. For 7 months storage period, the seed moisture content is 7.49%, seed electrical conductivity 0.025μs/cm/g, seed thousand (1000) dry weights is 28g, and ability of seed to germinate normally is 20%. It was therefore concluded that different seed storage period would influence the rice seed quality measured.